Fractional Flow Reserve Evaluation and Chronic Kidney Disease: Analysis From a Multicenter Italian Registry (the FREAK Study). Issue 4 (31st December 2015) - Tebaldi, Matteo; Biscaglia, Simone; Fineschi, Massimo; Manari, Antonio; Menozzi, Mila; Secco, Gioel Gabrio; Di Lorenzo, Emilio; D'Ascenzo, Fabrizio; Fabbian, Fabio; Tumscitz, Carlo; Ferrari, Roberto; Campo, Gianluca
Abstract : Objectives: To establish if the presence of chronic kidney disease (CKD) influences fractional flow reserve (FFR) value in patients with intermediate coronary stenosis. Background: FFR‐guided coronary revascularization reduces cardiac adverse events in patients with coronary artery disease. CKD impairs microcirculation and increases cardiovascular risk. Whether CKD presence may limit FFR accuracy is unknown. Methods: We used data from a multicenter prospective registry enrolling 1.004 patients undergoing FFR evaluation for intermediate stenosis. We assessed the relationship between clinical and angiographic variables and FFR measurement. CKD was defined as CrCl value ≤45 ml/min. FFR value was considered potentially flow‐limiting, and therefore positive, if ≤0.80. The index of microcirculatory resistance (IMR) was calculated in 20 patients stratified according CrCl value (single‐center substudy). Results: FFR measurement was positive in 395 (39%) patients. Overall, 131 (13%) patients had CKD. Patients with CrCl ≤45 ml/min showed significantly higher FFR values as compared to the others (0.84 ± 0.07 vs. 0.81 ± 0.08, p  < 0.001). Positive FFR occurrence was lower in patients with CrCl ≤45 ml/min (27% vs. 41%, p  < 0.01). After multivariable analysis, diabetes (HR 1.07, 95%CI 1.008–1.13, p  = 0.03), left anterior descending (HR 1.35, 95%CI 1.27–1.43, p  < 0.001) and CrCl ≤45 ml/min (HR 0.92, 95%CI 0.87–0.97, p  = 0.005) emerged as independent predictors of FFR measurement. Accordingly, IMR values were higher in patients with CrCl ≤45 ml/min (32 U [28245] vs. 16 U [11220], p  < 0.01). Conclusions: FFR and IMR measurements differ between CKD patients and those with normal renal function. Flow‐limiting FFR is less frequent in patients with CrCl ≤45 ml/min. © 2015 Wiley Periodicals, Inc.